1988
DOI: 10.1558/jmea.v1i1.111
|View full text |Cite
|
Sign up to set email alerts
|

The 'Royal Tombs' at Salamis (Cyprus)

Abstract: The rich burial assemblages ('Royal Tombs') excavated in a cemetery to the west of the ancient burial city of Salamis on the eastern coast of Cyprus have attracted widespread notice. Standard interpretations of these Iron Age burials characterize them simple as ostentatious displays by a few petty kings of Salamis with a mixture of Near Eastern and 'Homeric' styles and formats. The focus of this article is a re-examination of these burial assemblages in light of the major political, social and economic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Features such as horse and chariot or cart burials in some of these tombs, the inclusion of an ivory throne in one of them, a sword with silver rivets in another, and the very occasional evidence of human sacrifice or of the use of cremation have been hailed by some as deliberate reflections of Homeric epic (Coldstream 1977, 349–50; Karageorghis 1982, 131–5), and it has been suggested that, as such, these may be linked with a wider sense of pan‐hellenic consciousness disseminated as far as Cyprus through the medium of the Homeric epics at this time (cf. also Rupp 1988, 133). However, as a former proponent of ‘Homeric’ features in the Salamis Royal Tombs has recently observed, the fascination of the wonderful world of Homer may have prejudiced attempts to interpret these princely burials (Karageorghis 1995, 10), and when one looks closely at both the tombs and their heterogeneous assemblage of contents 19 one cannot fail to agree with him.…”
Section: Cyprus: Script and Identity Without Homermentioning
confidence: 92%
See 1 more Smart Citation
“…Features such as horse and chariot or cart burials in some of these tombs, the inclusion of an ivory throne in one of them, a sword with silver rivets in another, and the very occasional evidence of human sacrifice or of the use of cremation have been hailed by some as deliberate reflections of Homeric epic (Coldstream 1977, 349–50; Karageorghis 1982, 131–5), and it has been suggested that, as such, these may be linked with a wider sense of pan‐hellenic consciousness disseminated as far as Cyprus through the medium of the Homeric epics at this time (cf. also Rupp 1988, 133). However, as a former proponent of ‘Homeric’ features in the Salamis Royal Tombs has recently observed, the fascination of the wonderful world of Homer may have prejudiced attempts to interpret these princely burials (Karageorghis 1995, 10), and when one looks closely at both the tombs and their heterogeneous assemblage of contents 19 one cannot fail to agree with him.…”
Section: Cyprus: Script and Identity Without Homermentioning
confidence: 92%
“… 20 Indeed, in general there is a greater resemblance between the general ‘style’ of these tombs and the Royal Graves at Ur, the Phrygian royal graves at Gordion, and even the Mycenae Shaft Graves – possibly, as Rupp (1988, 132) has pointed out, for similar reasons to do with the enhancement of local political power structures. …”
mentioning
confidence: 98%
“…There is no evidence for pitch linings in the early Archaic amphoras, either from Kekova Adası or elsewhere, but neither should a lack of pitch be considered conclusive for a non‐wine content. In fact, if the primary production‐centre for early Archaic basket‐handle amphoras was the eastern part of Cyprus—perhaps even around Salamis—as preliminary visual observation of their fabric suggests, then oil and wine are certainly both plausible; the Iron Age kingdom controlled a region suitable for a wide range of cultivation, including olives, grapes and cereal (Rupp, 1988: 130–31). While the quantity of basket‐handle jars on the Kekova Adası site might suggest that they were purpose‐made for a bulk shipment, it cannot yet be ascertained whether these vessels saw use in a primary or secondary transport context, nor whether they all held the same contents or were the products of a single workshop.…”
Section: Kekova Adasımentioning
confidence: 99%
“…Whereas Iacovou (2013, p. 37) has argued that the process leading to the formation of the Cypro-Archaic polities must have begun no later than the twelfth century bc, the details of that process remain vague and contentious, particularly in the absence of settlement data and the over-reliance on evidence from cemeteries, sanctuaries, inscriptions and foundation myths (e.g. Rupp, 1988;Vanschoonwinkel & Karageorghis, 1994;Papantoniou, 2012a;Fourrier, 2013;Janes, 2013). Iacovou (2013) suggested that Cypriot polities had an inherent frailty, in part the result of environmental constraints but also partly due to a reliance on the-at times-industrial level of outward-bound trade in copper metal; using ancient Cyprus's abundant forests for fuel, metallic copper was extracted from the massive sulphide ore deposits within the Pillow Lavas that encircle the central Troodos mountain range.…”
Section: Introductionmentioning
confidence: 99%